Healthy Cities. - Kent, Jennifer L.; Thompson, Susan (Palgrave Macmillan, 2020)
The way urban structure and governance influence human health is the subject of a burgeoning body of research. The chapter provides a critical examination of this emergent health and urban planning nexus. The chapter opens with an overview of the condition of health and urban planning in modern cities. It proposes the concept of a ‘healthy built environment’ to review some of the most common risk factors associated with the way people live in cities, and shows how cities can be planned and managed to address these health risks. The chapter concludes with reflections on key challenges for healthy built environments, with a particular emphasis on ensuring that cities are fair and equitable for all.
Keywords: Stadtplanung; Gesundheit; Gesundheitsrisiko